Inclusion and work: addressing the global challenges for youth employment. Issue 2 (14th March 2018) - Dhakal, Subas P.; Connell, Julia; Burgess, John
Abstract : Purpose: The purpose of this paper is to outline the key global challenges relating to youth employment and consider some ways that they may be addressed to allow their inclusion in the contemporary workplace. Also, the paper provides a brief introduction and rationale for the other five articles comprising this special issue volume. Design/methodology/approach: The approach concerns a review of the relevant literature and reports on the topic. Findings: The challenges outlined in this paper and the others in this special issue volume emphasise the need for much more work to be done to address the current global challenges relating to youth unemployment. It points to: the difficulties many young workers face in taking the first step towards gaining employment; the need for stakeholder collaboration towards future policy investment as well as strategy implementation and integration. Originality/value: To date, much of the research that has been conducted on the challenges of youth employment and inclusion appears to have focussed on Europe and the USA. This special issue volume includes countries that have been less researched to date: Australia, Indonesia, Malaysia, Mauritius, Singapore and the United Arab Emirates, thus adding to current understanding of the topic in those contexts.